2020
DOI: 10.1108/jpcc-08-2019-0020
|View full text |Cite
|
Sign up to set email alerts
|

The design and validation of the enabling conditions for collective teacher efficacy scale (EC-CTES)

Abstract: PurposeHigh levels of collective teacher efficacy (CTE) within a school is known to be associated with improved student learning. CTE is a marker of the level of shared efficacy among teachers within a school. Knowledge of the levels of CTE within a school does not, though, support its development. To properly support school leaders in nurturing CTE, knowledge of the status of the enabling conditions for CTE within their schools is necessary to identify areas of strength and opportunities for improvement. Arme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
53
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(58 citation statements)
references
References 38 publications
2
53
1
2
Order By: Relevance
“…However, our findings are contradictory to reports of scales based on the theory [44], which divided the construct into two dimensions (cohesion and social control) [35,38,44]. Similar to recent research [76], we think these scales evaluate the group's conditions or characteristics that allow developing collective teacher efficacy, but not the perception of group capability. Even so, further studies should integrate the two perspectives to better understand the construct.…”
Section: Dimensionality Hypothesiscontrasting
confidence: 90%
“…However, our findings are contradictory to reports of scales based on the theory [44], which divided the construct into two dimensions (cohesion and social control) [35,38,44]. Similar to recent research [76], we think these scales evaluate the group's conditions or characteristics that allow developing collective teacher efficacy, but not the perception of group capability. Even so, further studies should integrate the two perspectives to better understand the construct.…”
Section: Dimensionality Hypothesiscontrasting
confidence: 90%
“…However, they also found that school processes that promote teacher ownership of school directions (shared school goals, school-wide decision-making, the fitting of plans to school needs and empowering principal leadership) exert an even stronger influence on CTE than prior student achievement. Donohoo et al. (2020) identified five enabling conditions that support the cultivation of CTE: empowered teachers, embedded reflective practices, cohesive teacher knowledge, goal consensus and supportive leadership.…”
Section: Research Around the Worldmentioning
confidence: 99%
“…This tool can assess collective efficacy among teachers in the school context as a reliable and valid instrument. Although few studies validate the scale ( Sánchez-Rosas et al, 2021 ) and others create a new scale based on it ( Donohoo et al, 2020 ; Kapat et al, 2022 ), there is no consensus on its dimensionality. Also is shorter than the previous version, which is especially important in school contexts where there is less time to participate in studies.…”
Section: Discussionmentioning
confidence: 99%
“…Other measures have been developed based on Goddard’s research. The Collective Teacher Efficacy Scale (EC-CTES; Donohoo et al, 2020 ) addresses advanced teacher influence, goal consensus, knowledge of others’ work, cohesive staff, leadership responsiveness, and Effective Systems of Intervention. Collective Teacher Self-Efficacy Scale ( Sánchez-Rosas et al, 2021 ) is a self-report instrument that measures beliefs about the capabilities of the teaching team.…”
Section: Introductionmentioning
confidence: 99%